EFFECT OF CARBOHYDRATE (STARCH) LEVEL IN PURIFIED DIETS ON THE GROWTH OF PENAEUS INDICUS - Ali, Syed Ahmed (Indian Journal of Fisheries, 2011)
Four purified diets were formulated using casein, gelatin, starch, fish oil,groundnut oil, vitainins, minerals and cellulose. The carbohydrate in the dietsiwas increased from 10 to 40% Tay varying the starch content to study the effectof dietary carbohydrate level on the growth, survival and food conversion of theprawn Penaeus indicus The protein and the lipid contents were kept constant inall the diets. Feeding experiments conducted in the laboratory on the juvenileP. indicus indicated that the growth of prawn increased with increase in the dietarycarbohydrate level from 10 to 40% (P